Folate status in Aboriginal people before and after mandatory fortification of flour for bread-making in Australia - Bower, C.; Maxwell, S.; Hickling, S.; D'Antoine, H.; O'Leary, Peter (2015)
Background: Mandatory fortification of wheat flour for bread-making was introduced in Australia in September 2009, to assist in the prevention of neural tube defects (NTD). NTD are twice as common in Aboriginal compared with non-Aboriginal infants, and folate levels are lower in the Aboriginal population. Aims: This study was undertaken to compare folate status and NTD in the Aboriginal population before and after fortification. Methods: Postfortification, 95 Aboriginal men and nonpregnant women aged 16–44 years in metropolitan and regional Western Australia (WA) completed a rapid dietary assessment tool and had blood taken to measure red cell folate. Measures were compared with prefortification values obtained in an earlier study using the same methods. Data on NTD in Aboriginal infants were obtained from the WA Register of Developmental Anomalies. Results: No participant was folate deficient. The mean red cell folate increased after fortification to 443 ng/mL for males and 567 ng/mL for females. The mean difference between red cell folate after fortification compared with before was 129 ng/mL for males (95% CI 81–177); t = 5.4; P < 0.0001) and 186 ng/mL for females (95% CI 139–233); t = 7.9; P < 0.0001). Most participants ate fortified shop-bought bread at least weekly, resulting in an estimated additional folate intake per day of 178 (males) and 145 (females) dietary folate equivalents. NTD prevalence fell by 68% following fortification (prevalence ratio 0.32 (CI 0.15–0.69)). Conclusions: The population health intervention of mandatory fortification of wheat flour for bread-making has had the desired effect of increasing folate status and reducing NTD in the Australian Aboriginal population.